The safety of artemisinins during pregnancy: a pressing question - Dellicour, Stephanie (BioMed Central, 2007)
BACKGROUND: An increasing number of countries in sub-Saharan Africa are changing to artemisinins combination therapy (ACT) as first or second line treatment for malaria. There is an urgent need to assess the safety of these drugs in pregnant women who may be inadvertently exposed to or actively treated with ACTs. OBJECTIVES: To examine existing published evidence on the relationship between artemisinin compounds and adverse pregnancy outcomes and consider the published evidence with regard to the safety of these compounds when administered during pregnancy. METHODS: Studies on ACT use in pregnancy were identified via searches of MEDLINE, EMBASE, Cochrane and Current Contents databases. Data on study characteristics, maternal adverse events, pregnancy outcomes and infant follow up were extracted. RESULTS: Fourteen relevant studies (nine descriptive/case reports and five controlled trials) were identified. Numbers of participants in these studies ranged from six to 461. Overall there were reports on 945 women exposed to an artemisinin during pregnancy, 123 in the 1st trimester and 822 in 2nd or 3rd trimesters. The primary end points for these studies were drug efficacy and parasite clearance. Secondary endpoints were birth outcomes including low birth weight, pre-term birth, pregnancy loss, congenital anomalies and developmental milestones. While none of the studies found evidence for an association between the use of artemisinin compounds and increased risk of adverse pregnancy outcomes, none were of sufficient size to detect small differences in event rates that could be of public health importance. Heterogeneity between studies in the artemisinin and comparator drugs used, and in definitions of adverse pregnancy outcomes, limited any pooled analysis. CONCLUSION: The limited data available suggest that artemisinins are effective and unlikely to be cause of foetal loss or abnormalities, when used in late pregnancy. However, none of these studies had adequate power to rule out rare serious adverse events, even in 2(nd )and 3(rd )trimesters and there is not enough evidence to effectively assess the risk-benefit profile of artemisinin compounds for pregnant women particularly for 1(st )trimester exposure. Methodologically rigorous, larger studies and post-marketing pharmacovigilance are urgently required.